2017
DOI: 10.1080/10810730.2017.1296510
|View full text |Cite
|
Sign up to set email alerts
|

Mobile But Connected: Harnessing the Power of Self-Efficacy and Group Support for Weight Loss Success through mHealth Intervention

Abstract: Despite the growing popularity of mHealth applications, their usage outcomes have received limited empirical attention. Drawing on server-level user activity data and an online survey (N = 384), this study examines the use of an mHealth application for weight loss to elucidate the ways in which it can help individuals harness the power of self-efficacy and group support to enact behavior change and accomplish their health goals. The results of structural equation modeling based on 6-month user activity data de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 42 publications
0
57
0
3
Order By: Relevance
“…Studies were excluded for multiple reasons, such as not having an intervention component (see Data S3 for a list of the excluded studies). In total, 41 studies had investigated the effectiveness of app‐based mobile interventions for improving nutrition behaviours or nutrition‐related health outcomes and met all four eligibility criteria. These 41 studies were then included in the systematic review and quantitative meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were excluded for multiple reasons, such as not having an intervention component (see Data S3 for a list of the excluded studies). In total, 41 studies had investigated the effectiveness of app‐based mobile interventions for improving nutrition behaviours or nutrition‐related health outcomes and met all four eligibility criteria. These 41 studies were then included in the systematic review and quantitative meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 41 studies, 29 included an app‐based assessment of the total nutrition intake, nine an assessment of specific foods such as vegetables or specific food consumption patterns (eg, adherence to specific guideline‐based recommendations), one assessed meal replacements, and two did not provide further information . Twenty one of the 32 studies that provided information about the features implemented for nutrition assessment included a database that participants could search to select the food items and meals they had consumed.…”
Section: Resultsmentioning
confidence: 99%
“…In a multiple regression analysis, Sherifali et al 31 reported non-significant effects of website login frequency and lesson unit completion on a 1-year weight loss (controlling for age and gender). Finally, in a structural equation analysis, Kim et al 32 reported that increased group participation and food logging frequency were predicted in a 6-month weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the efficacy of mHealth apps is provided across various weight management outcomes. Food logging frequency, 37 dietary restraint, eating concern, 38 eating goal awareness, 30 and intention to increase fruit and vegetable consumption 39 were found to increase following app use. On the other hand, overeating, 23 craving, 23 and eating disorder symptoms 38 were shown to decrease.…”
Section: Nonrandomized Studiesmentioning
confidence: 92%